Exploration of Local Wisdom in Land Dispute Resolution in South Central Timor District - Don Rade, Stefanus; Peter Lay, Benediktus (Journal of Law, Politic and Humanities, 2024)
The increasing population density often leads to differences in views that can eventually trigger disputes, including disputes related to land. Based on the increasing population level, of course the need for land as a place to live and make a business is getting narrower because the land has been controlled by other communities, while other communities also need land to carry out the same activities, this is where the dispute occurs. The method used in this research is empirical juridical research. The results show that the characteristics of dispute cases that occur in Oel'ekam Village include inherited land disputes, customary land disputes and land boundary disputes. The form of local wisdom in the Oel'ekam Village community is oko mama and the advantages of this alternative resolution are that the settlement is quickly realized, low cost, confidential and unemotional while there are also weaknesses, namely the execution mechanism which is difficult because the way to execute the decision, depends on the good faith of the parties to resolve the dispute to completion and the mediator will not bring good results especially if insufficient information and authority is given to him.